Iron poisoning - Durmuş, Ensar; Güneysu, Fatih (Journal of Surgery and Medicine, 2020)
Iron, represented by Fe on the periodic table, is the fourth most common element found on Earth. Although it has important tasks in the human body such as oxygen transfer, DNA synthesis, and electron exchange, it may also become toxic and harmful in excess. The toxicity of iron poisoning starts to appear with an intake of 20 mg/kg of elementary iron ions, along with GIS symptoms. In iron poisoning, patients usually present with various clinical findings and symptoms such as nausea, vomiting, palpitation, metabolic acidosis, deteriorated respiration, or mental disorders varying up to coma. Intervention in all patients begins with ABC evaluation, obtaining vascular access, monitoring, and (if necessary) providing oxygen support. Endotracheal intubation can be considered to ensure airway security and avoid aspiration, especially for lethargic patients. After abdominal and intestinal lavage, IV support treatment can begin, considering the liquid-electrolyte deficiency of these patients. In patients with a poor general condition and toxic appearance, hemogram, serum iron levels, kidney function tests, liver function tests, serum electrolytes, coagulation panel, arterial or venous blood gas, lactate, and in women of childbearing age, β-Hcg tests should be obtained. Abdominal radiography can be planned in the early stage. In patients thought to have serious iron poisoning, chelation treatment with deferoxamine is administered without delay.